Deseadan Archaeohyracidae (Notoungulata) from Quebrada Fiera (Mendoza, Argentina) in the paleobiogeographic context of the South American late Oligocene - Cerdeño Serrano, Maria Esperanza (2010)
Recent field work at the Deseadan (late Oligocene) locality of Quebrada Fiera (Mendoza Province, Argentina) has provided new fossil remains that greatly increased the faunal assemblage of this site. A good number of specimens correspond to the Family Archaeohyracidae (Notoungulata) and are presented in this paper. Most of them are recognized as a unique taxon, corresponding to the genus Archaeohyrax, characterized by the presence of a strong, shallow, wide sulcus on the labial side of the talonid of m3. At specific level, it is identified with the species A. suniensis previously recognized at Salla (Bolivia). Specimens with different tooth wear degree show an intraspecific variation in occlusal morphology comparable to that observed among the Bolivian material. In addition to A. suniensis, an isolated p2 is tentatively related to Archaeotypotherium, due to their hypsodont but rooted condition and larger size. Two other isolated lower molars from this site had been previously related to this genus but they are comparable to the new specimens ascribed to Archaeohyrax. The identification of Archaeotypotherium is not well supported at present, but if later confirmed, it would increase the temporal distribution of the genus, so far recorded in Tinguirirican (early Oligocene) localities of Chile and Argentina. The recognition of A. suniensis in Quebrada Fiera establishes a greater affinity with the lower latitude Deseadan fauna of Salla than with that from Patagonia, where the genus is represented by A. patagonicus. Other faunal elements from Quebrada Fiera, however, do not support this affinity with Bolivia. Xenarthrans or some marsupials are equivalent to those from Patagonia, while other taxa such as the recently described notohippid or a rare, tiny metatheria are at present exclusive for Mendoza. The increasing knowledge of the Quebrada Fiera assemblage contributes to a better understanding of the paleogeographic scenario of Southern South America during late Oligocene.Archaeohyrax, characterized by the presence of a strong, shallow, wide sulcus on the labial side of the talonid of m3. At specific level, it is identified with the species A. suniensis previously recognized at Salla (Bolivia). Specimens with different tooth wear degree show an intraspecific variation in occlusal morphology comparable to that observed among the Bolivian material. In addition to A. suniensis, an isolated p2 is tentatively related to Archaeotypotherium, due to their hypsodont but rooted condition and larger size. Two other isolated lower molars from this site had been previously related to this genus but they are comparable to the new specimens ascribed to Archaeohyrax. The identification of Archaeotypotherium is not well supported at present, but if later confirmed, it would increase the temporal distribution of the genus, so far recorded in Tinguirirican (early Oligocene) localities of Chile and Argentina. The recognition of A. suniensis in Quebrada Fiera establishes a greater affinity with the lower latitude Deseadan fauna of Salla than with that from Patagonia, where the genus is represented by A. patagonicus. Other faunal elements from Quebrada Fiera, however, do not support this affinity with Bolivia. Xenarthrans or some marsupials are equivalent to those from Patagonia, while other taxa such as the recently described notohippid or a rare, tiny metatheria are at present exclusive for Mendoza. The increasing knowledge of the Quebrada Fiera assemblage contributes to a better understanding of the paleogeographic scenario of Southern South America during late Oligocene.A. suniensis previously recognized at Salla (Bolivia). Specimens with different tooth wear degree show an intraspecific variation in occlusal morphology comparable to that observed among the Bolivian material. In addition to A. suniensis, an isolated p2 is tentatively related to Archaeotypotherium, due to their hypsodont but rooted condition and larger size. Two other isolated lower molars from this site had been previously related to this genus but they are comparable to the new specimens ascribed to Archaeohyrax. The identification of Archaeotypotherium is not well supported at present, but if later confirmed, it would increase the temporal distribution of the genus, so far recorded in Tinguirirican (early Oligocene) localities of Chile and Argentina. The recognition of A. suniensis in Quebrada Fiera establishes a greater affinity with the lower latitude Deseadan fauna of Salla than with that from Patagonia, where the genus is represented by A. patagonicus. Other faunal elements from Quebrada Fiera, however, do not support this affinity with Bolivia. Xenarthrans or some marsupials are equivalent to those from Patagonia, while other taxa such as the recently described notohippid or a rare, tiny metatheria are at present exclusive for Mendoza. The increasing knowledge of the Quebrada Fiera assemblage contributes to a better understanding of the paleogeographic scenario of Southern South America during late Oligocene.previously recognized at Salla (Bolivia). Specimens with different tooth wear degree show an intraspecific variation in occlusal morphology comparable to that observed among the Bolivian material. In addition to A. suniensis, an isolated p2 is tentatively related to Archaeotypotherium, due to their hypsodont but rooted condition and larger size. Two other isolated lower molars from this site had been previously related to this genus but they are comparable to the new specimens ascribed to Archaeohyrax. The identification of Archaeotypotherium is not well supported at present, but if later confirmed, it would increase the temporal distribution of the genus, so far recorded in Tinguirirican (early Oligocene) localities of Chile and Argentina. The recognition of A. suniensis in Quebrada Fiera establishes a greater affinity with the lower latitude Deseadan fauna of Salla than with that from Patagonia, where the genus is represented by A. patagonicus. Other faunal elements from Quebrada Fiera, however, do not support this affinity with Bolivia. Xenarthrans or some marsupials are equivalent to those from Patagonia, while other taxa such as the recently described notohippid or a rare, tiny metatheria are at present exclusive for Mendoza. The increasing knowledge of the Quebrada Fiera assemblage contributes to a better understanding of the paleogeographic scenario of Southern South America during late Oligocene.A. suniensis, an isolated p2 is tentatively related to Archaeotypotherium, due to their hypsodont but rooted condition and larger size. Two other isolated lower molars from this site had been previously related to this genus but they are comparable to the new specimens ascribed to Archaeohyrax. The identification of Archaeotypotherium is not well supported at present, but if later confirmed, it would increase the temporal distribution of the genus, so far recorded in Tinguirirican (early Oligocene) localities of Chile and Argentina. The recognition of A. suniensis in Quebrada Fiera establishes a greater affinity with the lower latitude Deseadan fauna of Salla than with that from Patagonia, where the genus is represented by A. patagonicus. Other faunal elements from Quebrada Fiera, however, do not support this affinity with Bolivia. Xenarthrans or some marsupials are equivalent to those from Patagonia, while other taxa such as the recently described notohippid or a rare, tiny metatheria are at present exclusive for Mendoza. The increasing knowledge of the Quebrada Fiera assemblage contributes to a better understanding of the paleogeographic scenario of Southern South America during late Oligocene., an isolated p2 is tentatively related to Archaeotypotherium, due to their hypsodont but rooted condition and larger size. Two other isolated lower molars from this site had been previously related to this genus but they are comparable to the new specimens ascribed to Archaeohyrax. The identification of Archaeotypotherium is not well supported at present, but if later confirmed, it would increase the temporal distribution of the genus, so far recorded in Tinguirirican (early Oligocene) localities of Chile and Argentina. The recognition of A. suniensis in Quebrada Fiera establishes a greater affinity with the lower latitude Deseadan fauna of Salla than with that from Patagonia, where the genus is represented by A. patagonicus. Other faunal elements from Quebrada Fiera, however, do not support this affinity with Bolivia. Xenarthrans or some marsupials are equivalent to those from Patagonia, while other taxa such as the recently described notohippid or a rare, tiny metatheria are at present exclusive for Mendoza. The increasing knowledge of the Quebrada Fiera assemblage contributes to a better understanding of the paleogeographic scenario of Southern South America during late Oligocene.Archaeohyrax. The identification of Archaeotypotherium is not well supported at present, but if later confirmed, it would increase the temporal distribution of the genus, so far recorded in Tinguirirican (early Oligocene) localities of Chile and Argentina. The recognition of A. suniensis in Quebrada Fiera establishes a greater affinity with the lower latitude Deseadan fauna of Salla than with that from Patagonia, where the genus is represented by A. patagonicus. Other faunal elements from Quebrada Fiera, however, do not support this affinity with Bolivia. Xenarthrans or some marsupials are equivalent to those from Patagonia, while other taxa such as the recently described notohippid or a rare, tiny metatheria are at present exclusive for Mendoza. The increasing knowledge of the Quebrada Fiera assemblage contributes to a better understanding of the paleogeographic scenario of Southern South America during late Oligocene.A. suniensis in Quebrada Fiera establishes a greater affinity with the lower latitude Deseadan fauna of Salla than with that from Patagonia, where the genus is represented by A. patagonicus. Other faunal elements from Quebrada Fiera, however, do not support this affinity with Bolivia. Xenarthrans or some marsupials are equivalent to those from Patagonia, while other taxa such as the recently described notohippid or a rare, tiny metatheria are at present exclusive for Mendoza. The increasing knowledge of the Quebrada Fiera assemblage contributes to a better understanding of the paleogeographic scenario of Southern South America during late Oligocene.A. patagonicus. Other faunal elements from Quebrada Fiera, however, do not support this affinity with Bolivia. Xenarthrans or some marsupials are equivalent to those from Patagonia, while other taxa such as the recently described notohippid or a rare, tiny metatheria are at present exclusive for Mendoza. The increasing knowledge of the Quebrada Fiera assemblage contributes to a better understanding of the paleogeographic scenario of Southern South America during late Oligocene.